Legal Aspects of Audit 10% Participating interest Management on Mahakam Block Working Area - Sipayung, Baren -; Manullang, Sardjana Orba; Siburian, Henry Kristian; Kamar, Karnawi -; Prihantini, Febrina Nafasati (Faculty of Law, Universitas Pekalongan, 2024)
The efforts of the local government of East Kalimantan Province and Kutai Kartanegara Regency to increase local revenue by proactively taking part in receiving a 10% Participating Interest (PI) offer in the Mahakam Block working area have been successful based on Permen ESDM No. 37 of 2016. The ministerial regulation stipulates that the legal subject for managing the 10% PI has several alternative forms of business entity, namely the old BUMD, new BUMD, or Regional Public Company (Perseroda). Based on these administrative procedures, the legal subject deemed to fulfill the requirements as a legal subject for the 10% PI Manager at the Mahakam WK is PT MMPKM which was formed as a Perseroda business entity. However, this has implications for the emergence of new norms regarding the definition and composition of Perseroda share ownership, as well as the legal subject requirements for managing a 10% PI between the Permen ESDM No. 37 of 2016 and the Regional Government Law, PP BUMD, and PP No. 35 of 2004. Furthermore, because of the scope of state finances, the negative implication is that local governments do not get the maximum regional income from dividends from BUMD holding company PT MMPKM.